PERILAKU BELAJAR MAHASISWA PRODI PPKn UNIVERSITAS RIAU DENGAN MENGGUNAKAN MEDIA SOSIAL SEBAGAI SARANA BELAJAR - Remenia Manalu; Supentri Supentri; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is based on lecture activities carried out through social media, due to the corona virus outbreak in Indonesia. Such conditions encourage educators to use social media as a learning tool, therefore lecturers at the Riau University Civics Study Program carry out the teaching and learning process using social media as has been applied at Riau University in order to keep learning created, even in the conditions of the Covid 19 outbreak. which limits students and lecturers from meeting face to face. Based on this phenomenon, a problem formulation was drawn, namely how the student learning behavior of the Riau University Civics Study Program was using social media. The purpose of this study was to determine the learning behavior of students in the Civics Study Program by using Social Media as a learning tool. In this study, the method used is descriptive quantitative. The data collection instrument used in this study is a questionnaire consisting of 27 questions from 11 indicators. The population of this study were students of the Riau University Civics Study Program. The sample in this study was taken by proportional stratified random sampling with a total sample of 68 people. Based on the results of the research conducted, it can be concluded that the learning behavior of students of the Riau University Civics Study Program using social media is in the "Good" category.Key Words: Learning behaviour,College student , Social Media